UNDERSTANDING THE IMPACT OF AIRPORT SERVICE QUALITY ON PASSENGERS’ REVISIT INTENTIONS AMIDST COVID-19 PANDEMIC - Parvinder Kour; Aruditya Jasrotia; Sudhanshu Gupta (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2020)
With the increased competitive scenario destination authorities are looking at every possible aspect for attracting the tourists by serving quality services. Airports around the world are looking for enhancing airport service quality thereby working towards overall travel satisfaction. Quality of service and consumer satisfaction is considered as critical determinant of strategic framework for determining any business performance. The current study aims to examine the impact of airport service quality on passengers’ revisit intentions amidst the COVID-19 pandemic and further its association with destination selection or choice. Crisis situations like COVID-19 immediately hit airports and therefore, it becomes absolutely essential for them to revive and adapt their services quickly according to the changing conditions. The SEM analysis was applied where satisfaction was observed as a mediator between airport service quality and travelers’ intent to revisit the airport, willingness to spend at the airport as well as their intent to come and visit again the destination. To this, positive and in fact significant relation has been observed between Airport Service Quality and willingness to spend at the airport and revisit the airport as well the destination. Since airports are amongst the service providers tourism destinations, this study gives the authorities with theoretical and empirical background to consider numerous factors that the passengers are actually looking in a service or might seek in future which currently is unclear and ambiguous due to COVID-19.